The role of community advisory boards in health research: Divergent views in the South African experience - Priscilla Reddy; David Buchanan; Sibusiso Sifunda; Shamagonam James; Nasheen Naidoo (Taylor & Francis Group, 2010)
In the light of the growing involvement of community advisory boards (CABs) in health research, this study presents empirical findings of the functions and operations of CABs in HIV/AIDS vaccine trials in South Africa. The individual and focus group interviews with CAB members, principal investigators, research staff, community educators, recruiters, ethics committee members, trial participants and South African AIDS Vaccine Initiative (SAAVI) staff members demonstrated differences in the respondents' perceptions of the roles and responsibilities of CABs. These findings question the roles of the CABs. Are they primarily there to serve and be accountable to the community, or to serve the accomplishment of the research objectives? Four emergent themes are discussed here: purpose; membership and representation; power and authority; sources of support and independence. The CABs' primary purpose carries significant implications for a wide range of issues regarding their functioning. The dual functions of advancing the research and protecting the community appear to be fraught with tension, and require careful reconsideration.